What makes people send gifts via social network services? A mixed methods approach. Issue 1 (29th July 2019) - Lee, So-Hyun; Choi, Su-Jin; Kim, Hee-Woong
Abstract : Purpose: Social network services (SNS) gifting is a new business model, but many SNS providers continue to face challenges as they explore ways to increase their revenues from gifting. The purpose of this paper is to examine the key factors involved in gift giving via SNS platforms. Design/methodology/approach: This study adopts a mixed methods approach through qualitative and quantitative research. In the first stage (qualitative study), the authors extract factors from interviews with users of SNS gifting services. In the second stage (quantitative study), the authors interpret decisional factors explored in the first stage on the basis of customer value theory, develop a research model and empirically test it. Findings: The results show that five factors – convenience of SNS gifting, symbolic representation of SNS gifting, relationship support of SNS gifting, pleasure of SNS gifting, and an SNS gifting norm – directly or indirectly affect SNS gifting decisions. Research limitations/implications: This study contributes to electronic commerce research by extending the customer value theory and adding to the literature on SNS gifting and gift giving in general. Practical implications: The study informs SNS providers regarding the promotion of SNS gifting services for revenue generation. Originality/value: This study is among the first to comprehensively examine decision-making in SNS gifting through the lens of customer value theory.